Keaktifan Peserta Didik melalui Metode Pembelajaran Interaktif di Homeschooling Kak Seto Surabaya - Lutfiani, Indah Tri; Nugroho, Rivo (J+PLUS UNESA, 2024)
This research aims to 1) describe and analyze students' active learning through interactive learning methods at Homeschooling Kak Seto Surabaya, 2) describe and analyze supporting factors in interactive learning methods at Homeschooling Kak Seto Surabaya and 3) describe and analyze inhibiting factors in learning methods interactive at Homeschooling Kak Seto Surabaya. The approach used in the research is descriptive qualitative. By using data collection techniques through the process of interviews, observation and documentation. In this research, researchers used data analysis using data collection, data reduction, data presentation, then finally drawing conclusions and verification. The results of this research are that by applying interactive learning methods it is able to foster an active learning attitude in Package A students, the learning process becomes more active and conducive because all students are actively involved in all learning activities so that it can increase students' interest in learning, when the students' learning process becomes more comfortable and not easy to make students bored. The supporting factors for this learning method are adequate facilities and infrastructure, active students, and creative tutors. The inhibiting factors in implementing this interactive learning method are network problems and power outages.